Performance accountability and combating corruption - Shah, Anwar (Public sector governance and accountability series., 2007)
This volume provides an analytical framework and operational approaches needed for the implementation of results-based accountability. The volume makes a major contribution to the literature on public management and evaluation. Major subject areas covered in this book include: performance based accountability, e-government, legal and institutional framework to hold government to account; fighting corruption; external accountability and the role of supreme audit institutions on detecting fraud and corruption.